2022
DOI: 10.1039/d2cp01712a
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-coupled borophene-based heterolayers for excitonic and molecular sensing applications

Abstract: Borophene (B), possessing remarkably unique chemical binding in its crystallographic structural phases including anisotropic structures, theoretically has high Young’s modulus as well as thermal conductivity and moreover, it is metallic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…As we discussed in the above sections that NPC was widely observed in various types of materials. ,,,, Different origin has been proposed for NPC generation, which can be suitable for various kind of applications. The NPC effect has been used for the fabrication of humidity and light sensors, highly sensitive photodetectors, and nonvolatile memories. , Qin et al demonstrated that the NPC in nanodiamonds can be applied for humidity sensors with the sensitivity of 1.26 × 10 6 %, which is the highest in carbon-based humidity sensors . Zhuang et al showed the application of NPC in humidity sensors with a responsivity of 418.1 μAW –1 (at high humid RH = 90%) .…”
mentioning
confidence: 99%
“…As we discussed in the above sections that NPC was widely observed in various types of materials. ,,,, Different origin has been proposed for NPC generation, which can be suitable for various kind of applications. The NPC effect has been used for the fabrication of humidity and light sensors, highly sensitive photodetectors, and nonvolatile memories. , Qin et al demonstrated that the NPC in nanodiamonds can be applied for humidity sensors with the sensitivity of 1.26 × 10 6 %, which is the highest in carbon-based humidity sensors . Zhuang et al showed the application of NPC in humidity sensors with a responsivity of 418.1 μAW –1 (at high humid RH = 90%) .…”
mentioning
confidence: 99%
“…In fact, room temperature electrical signal is very noisy. Therefore, room-temperature diagnosis tools such as scanning tunneling microscopy (STM) or current force microscopy (CAFM) based electrical signals for evaluating the quality of interfaces are being developed [ 253 ].…”
Section: Primary Challengesmentioning
confidence: 99%
“…Graphene and its inorganic analogues Xenes such as borophene, phosphorene, stanene, and germanene, 2D-gold, transition metal dichalcogenides (TMDCs), metal oxides (2DMOs), and MXenes (metal nitrides, carbides, and carbonitrides) due to their fascinating behavior have revolutionized materials science and technology where the corresponding bulk or nanomaterials do not compete with their 2D forms. They have successfully been employed in excitonics, in molecular sensing, as oxidation-resistant laminates, as a laser shield, and in manipulation of single-photon emission. Even though straining and hybridization have already been implemented to manipulate material properties, substitutional doping is the apt strategy to change the material intrinsically and irreversibly. Bandgap engineering in 2D materials is essential to meet the needs of electronic, optoelectronic, spintronic, and straintronic chips, as they are mechanically flexible at a few monolayer thicknesses. , While graphene gets oxidized, molybdenum disulfide (MoS 2 ) gets structurally degraded at elevated temperatures. Therefore, for high-temperature applications of these flexible, functional chips, one needs to explore 2D materials that can withstand high temperatures, keeping structural and chemical phase qualities intact.…”
Section: Introductionmentioning
confidence: 99%